Perbandingan Kekuatan Tarik Bahan Adhesif Resin Komposit Hibrid pada Braket Ortodontik terhadap Perbedaan Intensitas Sinar Tampak (Comparation of Tensile Strength Hybrid Composite Adhesive Material Resin at Orthodontic Brachet to Different Light Cure - Syamsinar .; Leliana Sandra Devi; Amiyatun Naini (Pustaka Kesehatan, 2015)
Hybrid composite resin it’s brachet adhesive agents of little and big particle bond. Light cure intensity influence hybrid composite resin polymmerisation. In orthodontic most research is about brachet bonding strength by using tensile strength test. The aim of this study was to determine the difference of tensile strength of hybrid resin composite on orthodontic brachet with different light cure intensity. Samples for this study ware upper maxilary jaw premolar tooth. Samples ware divided into two groups. Each groups was etched, bonded, and applied by hybride composite resin on base of brachet. Group 1 was exposed by light cure intensity at 650-850 mW/cm2, and group two with 2700 mW/cm2 intensity. Tensile strength test was done to know bracke bonding strength with teeth. The result of this study showed there was significant difference between tensile strength of light cure at 650-850 mW/cm2, and 2700 mW/cm2intensity with signifficant value 0.002 (p<0,005). Conclusion of this study that high light cure intensity had better brachet bonding strength than low light cure intensity.   Keywords: hybrid composite resin, light cure intensity, tensile strength.